2017
DOI: 10.5352/jls.2017.27.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Polyphenols and Antibiotics

Abstract: aureus) and gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa).These are found to be more efficient against the E. coli, L. monocytogenes, P. aeruginosa and S. aureus than antibiotics such as gentamicin and streptomycin. The kaempferol and quercetin showed synergistic effect with ciprofloxacin and rifampicin against S. aureus and methicillin resistant S. aureus (MRSA). Epigallocatechin gallate (EGCG) acts synergistically with various β-lactam antibiotics against MRSA. In particular, the epica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Interestingly, neither the combination of quercetin and penicillin G nor the combination of kaempferol-3,7-dirhamnoside and penicillin G appeared to synergistically inhibit the growth of representative strains tested in this study (data not shown). This is in agreement with a previous finding that kaempferol and quercetin had mild inhibitory effects on β-lactamase when used alone but exhibited excellent β-lactamase inhibition when used in combination with rifampicin ( 27 ). Therefore, the combined antibacterial effect of GE-EE with penicillin G was likely to depend on the interaction of kaempferol glycosides and quercetin with penicillin G. The combination of GE-EE with ceftazidime, erythromycin, levofloxacin, or vancomycin did not show a synergistic inhibitory activity against MRSA strains.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, neither the combination of quercetin and penicillin G nor the combination of kaempferol-3,7-dirhamnoside and penicillin G appeared to synergistically inhibit the growth of representative strains tested in this study (data not shown). This is in agreement with a previous finding that kaempferol and quercetin had mild inhibitory effects on β-lactamase when used alone but exhibited excellent β-lactamase inhibition when used in combination with rifampicin ( 27 ). Therefore, the combined antibacterial effect of GE-EE with penicillin G was likely to depend on the interaction of kaempferol glycosides and quercetin with penicillin G. The combination of GE-EE with ceftazidime, erythromycin, levofloxacin, or vancomycin did not show a synergistic inhibitory activity against MRSA strains.…”
Section: Resultssupporting
confidence: 93%
“…Ferulic acid is one of several phenols with antibacterial activity against pathogenic bacteria. Several reports found that ferulic acid had high antibacterial activity against E. coli and P. aeruginosa (MIC of E. coli and P. aeruginosa were 100 μg/mL) ( Borges et al, 2013 ; Cho et al, 2017 ). The possible mechanism for antimicrobial effect of phenolic compounds are known as altering microbial cell permeability, which interfering with membrane function such as nutrient uptake, electron transport, enzyme activity, protein and nucleic acid synthesis ( Abu-Salem et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of combinations of antibiotics and natural substances with antimicrobial properties may be an effective strategy. From these perspectives, polyphenols may increase the activity of traditional antibiotics used against a wide set of bacteria [27][28][29][30].…”
Section: Antibacterial Activities Of the Studied Tannins Applied Alon...mentioning
confidence: 99%